Schools and psychosocial development according to the perceptions of young individuals with ADHD - Rangel Júnior, Édison de Britto; Loos, Helga (Paidéia (Ribeirão Preto), 2011)
Individuals with ADHD seem to have a peculiar neurological functioning. Their cerebral hyperactivity, sometimes accompanied by physical hyperactivity, make individuals attention capabilities to become unstable, generating difficulties to adapt to the traditional school system. However, these individuals often prove to be creative and sensitive, and occasionally brilliant. This study investigated the perceptions of adolescents and young adults with ADHD diagnosis regarding the schools role in their psychosocial development, with an emphasis to identity aspects. A total of 21 former and current students were interviewed; data were videotaped and qualitatively analyzed. As evidenced in the literature, a high number of grade failures, expulsions, and compulsory transfers were observed among the participants as well as learning and behavioral disorders. Poor academic performance and negative labeling contributed to the individuals diminished perceptions concerning their abilities, who ended up building predominantly negatively self beliefs. The reports revealed the poor treatment delivered by schools to these students and a lack of alternatives to develop their potential and facilitate their adaptation to the school environment.